Social and moral-ethical bases of Islam in modern globalizing world (Journal of Philosophy Culture and Political Science, 2019)
In the article spared the questions of moral'no-eticheskoy idea of islam, social theories. A modern islam is in Kazakhstan, his difference by the tolerance, extremist or radical displays which meet in some regions of the world are alien him. Historically folded so, that an islam in Kazakhstan conducted a dialog with other religions on a collaboration. This line of dialog with all confessions of our country and religions of different countries of the world – remains lead in internal and external strategy of moslem